Feasibility Analysis of the Application of Project Loon as an Equitable Effort for Communication Infrastructure Development in Indonesia - Setiyo Budiyanto; Muhammad Jamil; Fajar Rahayu (InComTech : Jurnal Telekomunikasi dan Komputer, 2019)
In Indonesia, urban area internet users, between villages and cities, are arranged in the villages according to 72.41%, 49.5%, and 48.3%. Following are the composition of internet users in Indonesia: Java, Sumatra, Kalimantan, Sulawesi, Bali-Nusa Tenggara, and Maluku-Papua respectively 58.1%, 19%, 8%, 6.7%, 5.6%, and 2.5%. To overcome this problem, several attempts have been made to equalize internet access in Indonesia, and one of the efforts offered is Project Loon. Project Loon is a communication technology based on High Altitude Platform (HAPs). Research related to Project Loon feasibility testing is conducted using library study methods using SWOT analysis using strengths, weaknesses, advantages, and battles against Project Loon using various indicators such as systems, infrastructure, economy and regulation. The conclusion of this research is that Loon Project has the potential to be implemented not yet available in Indonesia. In terms of infrastructure and economy, Project Loon is quite effective and economical. However, it must still consider the population in the area to avoid operational costs.